2019
DOI: 10.1016/j.jaci.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor alpha signaling increases ILC2-mediated allergic airway inflammation

Abstract: RATIONALE: The purpose of this study was to determine whether conventionally used ILC2 markers, ST2 and CD127, are sufficient to include all Th2-cytokine producing ILCs. We hypothesized that ST2-and CD127-negative ILC2 populations exist in mouse lung and that these nontraditional populations might be activated by the clinically relevant fungal allergen Alternaria, a known potent inducer of IL-33. METHODS: Mice were challenged intranasally with Alternaria alternata for three consecutive days, and 24 hours after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study demonstrated that ERα signaling via promoting secretion of IL-33 cytokine augments the proliferation and activation of ILC2. 43 Moreover, it has been observed that the adoptive transfer of IL-4 + /IL-13 + ILC2 in the initiation phase of arthritis significantly attenuated inflammatory bone loss in both serum-induced arthritis (SIA) and collagen-induced arthritis (CIA) mice models, on the contrary IL-4 − /IL-13 − ILC2 failed to do the same. 44 Importantly, at later time points, even adoptive transfer of IL-4 + /IL-13 + ILC2 failed to suppress arthritis in SIA and CIA mice models.…”
Section: Innate Immune Cells and Osteoporosismentioning
confidence: 99%
“…A study demonstrated that ERα signaling via promoting secretion of IL-33 cytokine augments the proliferation and activation of ILC2. 43 Moreover, it has been observed that the adoptive transfer of IL-4 + /IL-13 + ILC2 in the initiation phase of arthritis significantly attenuated inflammatory bone loss in both serum-induced arthritis (SIA) and collagen-induced arthritis (CIA) mice models, on the contrary IL-4 − /IL-13 − ILC2 failed to do the same. 44 Importantly, at later time points, even adoptive transfer of IL-4 + /IL-13 + ILC2 failed to suppress arthritis in SIA and CIA mice models.…”
Section: Innate Immune Cells and Osteoporosismentioning
confidence: 99%